Enhanced Salt Tolerance Conferred by the Complete 2.3 kb cDNA of the Rice Vacuolar Na+/H+ Antiporter Gene Compared to 1.9 kb Coding Region with 5′ UTR in Transgenic Lines of Rice - Amin, U. S. M.; Biswas, Sudip; Elias, Sabrina M.; Razzaque, Samsad; Haque, Taslima; Malo, Richard; Seraj, Zeba I. (Frontiers in Plant Science, 2016)
Soil salinity is one of the most challenging problems that restricts the normal growth and production of rice worldwide. It has therefore become very important to produce more saline tolerant rice varieties. This study shows constitutive over-expression of the vacuolar Na+/H+ antiporter gene (OsNHX1) from the rice landrace (Pokkali) and attainment of enhanced level of salinity tolerance in transgenic rice plants. It also shows that inclusion of the complete un-translated regions of the alternatively spliced OsNHX1 gene provides a higher level of tolerance to the transgenic rice. Two separate transformation events of the OsNHX1 gene, one with 1.9 kb region containing the 5ʹ UTR with CDS and the other of 2.3 kb, including 5ʹ UTR, CDS and the 3ʹ UTR regions were performed. The transgenic plants with these two different constructs were advanced to the T3 generation and physiological and molecular screening of homozygous plants was conducted at seedling and reproductive stages under salinity (NaCl) stress. Both transgenic lines were observed to be tolerant compared to WT plants at both physiological stages. However, the transgenic lines containing the CDS with both the 5ʹ and 3ʹ UTR were significantly more tolerant compared to the transgenic lines containing OsNHX1 gene without the 3′ UTR. At the seedling stage at 12 dS/m stress, the chlorophyll content was significantly higher (P<0.05) and the electrolyte leakage significantly lower (P<0.05) in the order 2.3 kb> 1.9 kb> and WT lines. Yield in g/plant in the best line from the 2.3 kb plants was significantly more (P<0.01) compared respectively to the best 1.9 kb line and WT plants at stress of 6 dS/m. Transformation with the complete transcripts rather than the CDS may therefore provide more durable level of tolerance.